Pathogenicity OF Beauveria bassiana (bals) vuill. against the pumpkin plant butterfly Diaphania hyalinata (lepidoptera: pyralidae) in the laboratory - Lloclla Gonzáles, Herry (2017)
Entomopathógenic fungi are is obliged parasites that cause diseases in several orders of insects, constituting an ecological alternative in the pest Management in different agricultural cultures. In the present study, patogenicity of the Beauveria bassiana, for his potential application like microbiological control agent of against of the third instar larvae of the Pumpkin Plant butterfly Diaphania hyalinata (lepidoptera: pyralidae) some of the important pest of Pumpkin Plant butterfly. Isolation evaluated by direct application of conidias suspensions of 106 and 1010/ml and mortality registered on larvae of Diaphania hyalinata, between 19% to 68% in the four day. In conclusion the Beauveria bassiana presents a great potential as a microbiological control of Diaphania hyalinata. Key words: microbiology control, Beauveria bassiana, Diaphania hyalinata, pumpkin plant.